Manganese-containing graphene oxide composite material as well as preparation method and application thereof
By using potassium permanganate and ultrasonic stirring technology in the preparation process of graphene oxide, manganese-containing graphene oxide composite materials were prepared, which solved the problem of manganese ion pollution in wastewater and improved the removal efficiency of sulfur compounds.
Patent Information
- Application Number
- CN202310752004.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-25
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-06-25
AI Technical Summary
The existing graphene oxide preparation method produces high content of manganese ions in wastewater, which leads to environmental pollution problems and lacks effective methods to utilize manganese ions.
Potassium permanganate was added in batches after mixing graphite with concentrated acid. After heating and ultrasonic stirring and reflux reaction, a manganese-containing graphene oxide composite material was prepared to reduce the content of manganese ions in wastewater, and the specific surface area of the material was increased by ultrasonic stirring. To improve the removal effect.
It effectively reduces the content of manganese ions in wastewater, improves the removal effect of sulfur-containing compounds, solves the problem of environmental pollution, and reduces the preparation cost.
Smart Images

Figure BDA0004301533780000091 
Figure BDA0004301533780000101
Abstract
Description
Technical Field
[0001] The invention belongs to the field of graphene materials, and in particular relates to a manganese-containing graphene oxide composite material and a preparation method and application thereof. Background Art
[0002] Graphene oxide is an important type of graphite product, which can be used to prepare redox graphene, graphene and other popular downstream products. At present, the main method of producing graphene oxide is to oxidize graphite using strong oxidants such as potassium permanganate, but the wastewater produced by this method for preparing graphene oxide has a high manganese ion content, which is difficult to treat and is not suitable for direct discharge, and has great environmental pressure. Whether the manganese ions in the wastewater produced by the preparation of graphene oxide can be turned into resources is an important issue that scientific and technological workers need to think about and solve. Furthermore, whether it is possible to prepare a new manganese-containing composite material through technological innovation in the preparation process of graphene oxide is also a solution, but there are few related reports. Summary of the invention
[0003] The purpose of the present invention is to provide a manganese-containing graphene oxide composite material and a preparation method and use thereof. The manganese-containing graphene oxide composite material prepared by the present invention contains elements such as manganese, potassium, and sulfur, has a large specific surface area, and exhibits excellent performance in the reaction process of removing sulfur-containing compounds, and has a good removal effect. The preparation method provided by the present invention does not require the addition of sodium nitrate and hydrogen peroxide, reduces the content of manganese ions and the like in wastewater, and solves a series of problems such as environmental pollution.
[0004] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a manganese-containing graphene oxide composite material, the method comprising:
[0005] S1 After the graphite is mixed with concentrated acid, potassium permanganate is added in batches to obtain a first mixed solution;
[0006] S2: heating the first mixed solution to react, adding water and stirring to obtain a second mixed solution;
[0007] S3: subjecting the second mixed solution to a reflux reaction under ultrasonic stirring, and obtaining a manganese-containing graphene oxide composite material through solid-liquid separation;
[0008] Wherein, the reflux reaction conditions include: temperature of 100-200° C. and time of 2-72 h.
[0009] Optionally, the reflux reaction temperature is 120-180° C., and the time is 6-48 hours;
[0010] The ultrasonic stirring method is one or more of probe ultrasound or water bath ultrasound, the power is 50 to 500 W / h, and the stirring time is 0.1 to 12 h.
[0011] Optionally, the concentrated acid is selected from one or more of sulfuric acid, nitric acid and perchloric acid;
[0012] C0 is any concentration between N-10% and N+10%, preferably C0 is any concentration between N-5% and N+5%, C0 is the concentration of the concentrated acid, and N is the highest concentration of the analytical pure reagent grade of the concentrated acid.
[0013] Optionally, the graphite is one or more of natural flake graphite, natural cryptocrystalline graphite and artificial graphite;
[0014] The graphite has a carbon content of more than 95% by weight, an ash content of less than 1%, and a mesh size of 20 to 500 meshes.
[0015] Optionally, the mass ratio of the concentrated acid to the graphite is (15-100):1, preferably (25-80):1;
[0016] The mass ratio of the potassium permanganate to the graphite is (1-10):1, preferably (3-8):1;
[0017] The mass ratio of potassium permanganate to the graphite mixed in each batch is (0.1-1):1, preferably (0.2-0.5):1.
[0018] Optionally, the method further comprises:
[0019] In step S1, potassium permanganate is added in batches and mixed, and the temperature is controlled to be below 30° C., preferably below 20° C., and more preferably below 10° C., and stirred for 0.5 to 12 hours; sodium nitrate and hydrogen peroxide are not added during the reaction;
[0020] In step S2, the conditions for the heating reaction are: temperature of 35-60°C, reaction time of 0.2-6h; and time for stirring after adding water of 0.1-5h.
[0021] Optionally, the mass ratio of the amount of water added to the amount of graphite added is (20-500):1, preferably (50-200):1.
[0022] The second aspect of the present invention provides a manganese-containing graphene oxide composite material prepared by the method provided by the first aspect of the present invention.
[0023] Optionally, the manganese-containing graphene oxide composite material contains manganese, carbon, oxygen, potassium and sulfur, wherein the manganese content of the manganese element in terms of MnO2 is 55 to 90 weight %; the sulfur content in terms of SO2 is 0.5 to 10 weight %; the potassium content in terms of K2O is 1 to 15 weight %;
[0024] The XRD spectrum of the manganese-containing graphene oxide composite material has a characteristic peak of α-MnO2;
[0025] The specific surface area of the manganese-containing graphene oxide composite material is 300 to 800 m 2 / g, preferably 400 to 600 m 2 / g, the pore volume is 0.5 to 2 ml / g, preferably 0.8 to 1.5 ml / g, and the average particle size (size piece diameter) is 1 mm or less, preferably 0.5 mm or less.
[0026] The third aspect of the present invention provides use of the manganese-containing graphene oxide composite material according to the second aspect of the present invention in the removal of sulfur-containing compounds.
[0027] Through the above technical scheme, the manganese-containing graphene oxide composite material prepared by the present invention contains elements such as manganese, potassium, and sulfur, and exhibits excellent performance in the reaction process such as the removal of sulfur-containing compounds, and has a good removal effect. The preparation method provided by the present invention obtains a manganese-containing graphene oxide composite material by refluxing during ultrasonic stirring, so that the prepared manganese-containing graphene composite material has a large specific surface area. In the removal process of sulfur-containing compounds, the sulfur-containing compounds are more likely to contact the active center in the manganese-containing graphene oxide composite material, and the removal effect is improved; on the other hand, potassium permanganate is added in batches during the preparation process, and sodium nitrate and hydrogen peroxide do not need to be added during the reaction process, so that the content of manganese ions in the preparation wastewater is significantly reduced, solving a series of problems such as wastewater discharge polluting the environment.
[0028] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION
[0029] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.
[0030] A first aspect of the present invention provides a method for preparing a manganese-containing graphene oxide composite material, the method comprising:
[0031] S1 After the graphite is mixed with concentrated acid, potassium permanganate is added in batches to obtain a first mixed solution;
[0032] S2: heating the first mixed solution to react, adding water and stirring to obtain a second mixed solution;
[0033] S3 refluxes the second mixed solution under ultrasonic stirring to obtain a graphene composite material through solid-liquid separation;
[0034] The reflux reaction conditions include: a temperature of 100 to 200° C., preferably 120 to 180° C., more preferably 140 to 160° C., and a time of 2 to 72 h, preferably 6 to 48 h, more preferably 12 to 36 h.
[0035] The preparation method provided by the present invention prepares a manganese-containing graphene oxide composite material by performing a reflux reaction during ultrasonic stirring. In the above embodiment, by controlling the ultrasonic stirring and reflux reaction conditions within a preferred range for reaction, the prepared manganese-containing graphene oxide composite material has a large specific surface area, so that the accessibility of the active center of the reactant in the manganese-containing graphene oxide composite material is improved. In the removal process of sulfur-containing compounds, the sulfur-containing compounds are more likely to contact the active center in the manganese-containing graphene oxide composite material, the removal effect is improved, and a high removal rate is also achieved when the concentration of sulfur-containing compounds is high (greater than 1000ppm); on the other hand, potassium permanganate is added in batches during the reaction of graphite oxidation, and there is no need to add sodium nitrate and hydrogen peroxide, so that the content of manganese ions and the like in the preparation wastewater is significantly reduced, solving a series of problems such as wastewater discharge polluting the environment.
[0036] In a specific embodiment of the present invention, the ultrasonic stirring method is one or more of probe ultrasound or water bath ultrasound, the power is 50 to 500 W / h, preferably 100 to 300 W / h, and the stirring time is 0.1 to 12 h, preferably 0.5 to 6 h. In the above embodiment, the stirring time refers to the total time of ultrasonic stirring, excluding the time of intermittent stopping.
[0037] In a specific embodiment of the present invention, the concentrated acid is selected from one or more of sulfuric acid, nitric acid and perchloric acid, preferably sulfuric acid;
[0038] C0 is any concentration between N-10% and N+10%, preferably C0 is any concentration between N-5% and N+5%, C0 is the concentration of the concentrated acid, and N is the highest concentration of the analytical pure reagent grade of the concentrated acid.
[0039] In a specific embodiment of the present invention, the graphite is one or more of natural flake graphite, natural cryptocrystalline graphite and artificial graphite, preferably natural flake graphite;
[0040] The graphite has a carbon content of 99 wt % or more, preferably 99.9 wt % or more, an ash content of 1 wt % or less, preferably 0.1 wt % or less, and a mesh size of 20 to 500 meshes, preferably 50 to 200 meshes.
[0041] In a specific embodiment of the present invention, the mass ratio of the concentrated acid to the graphite is (15-100):1, preferably (25-80):1.
[0042] In a specific embodiment of the present invention, the mass ratio of the potassium permanganate to the graphite is (1-10):1, preferably (3-8):1.
[0043] The mass ratio of potassium permanganate to the graphite mixed in each batch is (0.1-1):1, preferably (0.2-0.5):1.
[0044] In a specific embodiment of the present invention, the method further comprises:
[0045] In step S1, potassium permanganate is added in batches and mixed, and the temperature is controlled to be below 30° C., preferably below 20° C., and more preferably below 10° C., and stirred for 0.5 to 12 hours, preferably 1 to 6 hours; no other substances such as sodium nitrate and hydrogen peroxide are added during the reaction;
[0046] In step S2, the conditions for the heating reaction are: temperature of 35-60°C, preferably 40-50°C, reaction time of 0.2-6h, preferably 0.5-3h; and time for stirring after adding water is 0.1-5h, preferably 0.2-1h.
[0047] In a specific embodiment of the present invention, the mass ratio of the amount of water added to the amount of graphite added is (20-500):1, preferably (50-200):1.
[0048] The second aspect of the present invention provides a manganese-containing graphene oxide composite material prepared by the method provided by the first aspect of the present invention.
[0049] The XRD spectrum of the manganese-containing graphene oxide composite material has a characteristic peak of α-MnO2.
[0050] The specific surface area of the manganese-containing graphene oxide composite material is 300 to 800 m 2 / g, preferably 400 to 600 m 2 / g, the pore volume is 0.5 to 2 ml / g, preferably 0.8 to 1.5 ml / g, and the average particle size is 1 mm or less, preferably 0.5 mm or less, and more preferably 0.2 mm or less.
[0051] In a specific embodiment of the present invention, the manganese-containing graphene oxide composite material contains manganese, carbon, oxygen, potassium and sulfur, which can effectively remove sulfides in sulfur-containing compounds and show excellent performance in the reaction process of removing and converting sulfur-containing compounds. Specifically, in the manganese-containing graphene oxide composite material, the content of manganese in terms of MnO2 is 55 to 90% by weight, preferably 65 to 80% by weight; the content of sulfur in terms of SO2 is 0.5 to 10% by weight, preferably 1 to 5% by weight; the content of potassium in terms of K2O is 1 to 15% by weight, preferably 2 to 10% by weight; the balance is C element.
[0052] The third aspect of the present invention provides use of the manganese-containing graphene oxide composite material according to the second aspect of the present invention in the conversion of sulfur-containing compounds.
[0053] The present invention is further illustrated by the following examples, but the present invention is not limited thereto.
[0054] The reagents used in the present invention are all commercially available analytically pure reagents. Among them, the carbon content of the flake graphite is more than 99.9 weight percent, the ash content is 0.09%, and the mesh size is 80 meshes.
[0055] Example 1
[0056] a. Add 150 ml of concentrated sulfuric acid (mass concentration greater than 98%) and 5 g of graphite into a beaker to obtain a mixed solution;
[0057] b. Add 25 g of potassium permanganate into the mixed solution obtained in step a in 5 batches, and stir and mix at 10° C. for 1 h to obtain a mixed material;
[0058] c. Stir the mixture obtained in step b at 40°C under autogenous pressure for 2h;
[0059] d. Add 150 ml of water to the mixture in step c, and continue stirring and reacting at 90° C. for 1 h to obtain a mixed slurry;
[0060] e. At 120° C. and autogenous pressure, the mixed slurry in step d was subjected to reflux reaction under ultrasonic stirring for 24 hours, the ultrasonic stirring mode was probe-type intermittent stirring, stirring for 5 minutes and stopping for 15 minutes, the power was 150 W, and the manganese-containing graphene oxide composite material was obtained by flash evaporation solid-liquid separation.
[0061] Example 2
[0062] The preparation method in Example 1 was adopted, except that, in step a, 100 ml of concentrated sulfuric acid was added.
[0063] Example 3
[0064] The preparation method in Example 1 was adopted, except that 15 g of potassium permanganate was added in step b.
[0065] Example 4
[0066] The preparation method in Example 1 was adopted, except that in step e, the reaction temperature was 160°C.
[0067] Example 5
[0068] The preparation method in Example 1 was adopted, except that in step e, the reflux reaction time under ultrasonic stirring was 20 min, and the power of ultrasonic stirring was 500 W.
[0069] Example 6
[0070] The preparation method in Example 1 was adopted, except that in step c, the reaction temperature was 30°C.
[0071] Example 7
[0072] The preparation method in Example 1 was adopted, except that in step d, 450 ml of water was added.
[0073] Example 8
[0074] The preparation method in Example 1 was adopted, except that in step b, the mass ratio of potassium permanganate to graphite added in each batch was 5:3, that is, potassium permanganate was added in 3 batches.
[0075] Example 9
[0076] The preparation method in Example 1 was adopted, except that in step a, 150 ml of concentrated nitric acid was added instead of concentrated sulfuric acid.
[0077] Comparative Example 1
[0078] The preparation method in Example 1 was adopted, except that in step e, ultrasonic stirring reflux reaction was not performed.
[0079] Comparative Example 2
[0080] The preparation method in Example 1 was adopted, except that in step e, the reflux reaction was not carried out under ultrasonic stirring, but under conventional mechanical stirring at a rotation speed of 250 rpm.
[0081] Comparative Example 3
[0082] The preparation method in Example 1 is adopted, except that in step b, 25 g of potassium permanganate is added once to the mixed solution obtained in step a.
[0083] Test Case
[0084] The element content of the sample was determined by XPS on a VGESCA-LABS X-ray photoelectron spectrometer, using Mg Kα X-rays as the laser source and the C1s binding energy (284.6 eV) of the surface contamination carbon to calibrate the binding energy of each element in the desulfurizer surface species.
[0085] The warm nitrogen adsorption-desorption test (BET) was carried out on a JW-BK200C surface area and pore size analyzer produced by Beijing Jingwei Gaobo Co., Ltd. The specific surface area and pore volume were calculated using the two-parameter BET equation, and the pore distribution was calculated using the BJH method.
[0086] The sulfide content in the sulfur-containing compounds before and after removal was analyzed by online chromatography (Nexis-2030, Shimadzu Corporation, Japan) and SCD fluorescence detector (SCD-2030).
[0087] 380 mg of the examples and comparative examples prepared by the present invention were loaded as removers into the constant temperature section of the reactor of a fixed bed micro reactor with an inner diameter of 10 mm and a length of 600 mm after passivation, and quartz sand was filled up and down. The sulfide content in the sulfur-containing compound raw material is 1500 ppm (the carrier gas is nitrogen, and the sulfide is a complex of hydrogen sulfide and carbonyl sulfide with a molar ratio of 2:1). The sulfide removal reaction was carried out at a flow rate of 150 ml / min at 30°C and 3MPa, and the sulfide content after the removal reaction was analyzed online, and then the sulfide removal rate was calculated. The results of the sulfide removal rate at 2h are shown in Table 1, and other characterization results of the prepared samples are shown in Table 2.
[0088] Table 1
[0089] Sulfur compound removal rate / % Example 1 99.7 Example 2 94.5 Example 3 90.2 Example 4 90.8 Example 5 88.4 Example 6 91.3 Example 7 85.9 Example 8 93.5 Example 9 83.2 Comparative Example 1 71.1 Comparative Example 2 77.4 Comparative Example 3 74.2
[0090] Table 2
[0091]
[0092]
[0093] According to the test results in Table 1 and Table 2, it can be seen that the manganese-containing graphene oxide composite material prepared by the preparation method provided by the present invention has a larger specific surface area and pore volume, a smaller average particle size, and can react with sulfur compounds. In the process of removing sulfur compounds from the material, it shows excellent performance in removing sulfur compounds, and the removal rate of sulfur compounds in the material reaches more than 90%. At the same time, the manganese ion content in the wastewater generated by the preparation of graphene oxide is reduced, and there is no need to add sodium nitrate and hydrogen peroxide during the reaction process, thereby reducing the cost of preparing the material.
[0094] It can be seen from the test results of Examples 1 to 9 that when the preparation method and the ultrasonic reflux reaction conditions are within the specified range of the present invention, the effect and performance of the product prepared by the present invention can be improved. By comparing Example 1 with Examples 2 to 9, it can be seen that when the type and amount of concentrated acid, the amount and batch of potassium permanganate, the heating temperature, the stirring time, and the mass ratio of the amount of water added to the amount of graphite added are all within the preferred specified range of the present invention, the performance of the manganese-containing graphene oxide composite material prepared by the present invention in removing sulfur compounds can be further improved.
[0095] From the test results of Comparative Examples 1 to 3, it can be seen that in Comparative Example 1, the reflux reaction was not carried out under ultrasonic stirring, and the graphene material was directly obtained by solid-liquid separation, which would result in the prepared material having a smaller specific surface area and pore size, a larger average particle size, a decrease in product quality, and a sulfide removal rate significantly lower than that of Example 1; in Comparative Example 2, the reflux reaction was carried out under conventional mechanical stirring conditions, and it was difficult to fully mix the materials, resulting in low material uniformity, resulting in the prepared graphene composite material having a small specific surface area and pore size, a large average particle size, poor product performance, and a sulfide removal rate significantly lower than that of Examples 1 to 9; in Comparative Example 3, potassium permanganate was added to the graphite at one time, which would cause the content of potassium permanganate adsorbed on the graphite to be uneven, and the reaction temperature rapidly rose to above 80°C, causing part of the material to splash, resulting in the prepared graphene composite material having a smaller specific surface area and pore volume, a larger average particle size, poor product performance, and a reduced sulfide removal rate in the material.
[0096] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0097] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0098] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a manganese-containing graphene oxide composite material, wherein: The method includes: S1 After the graphite is mixed with concentrated acid, potassium permanganate is added in batches to obtain a first mixed solution; S2: heating the first mixed solution to react, adding water and stirring to obtain a second mixed solution; S3: subjecting the second mixed solution to a reflux reaction under ultrasonic stirring, and obtaining a manganese-containing graphene oxide composite material through solid-liquid separation; Wherein, the reflux reaction conditions include: temperature of 100-200° C. and time of 2-72 h.
2. The method according to claim 1, wherein: The reflux reaction temperature is 120-180°C and the time is 6-48h; The ultrasonic stirring method is one or more of probe ultrasound or water bath ultrasound, the power is 50 to 500 W / h, and the stirring time is 0.1 to 12 h.
3. The method according to claim 1, wherein: The concentrated acid is selected from one or more of sulfuric acid, nitric acid and perchloric acid; C0 is any concentration between N-10% and N+10%, preferably C0 is any concentration between N-5% and N+5%, C0 is the concentration of the concentrated acid, and N is the highest concentration of the analytical pure reagent grade of the concentrated acid.
4. The method according to claim 1, wherein: The graphite is one or more of natural flake graphite, natural cryptocrystalline graphite and artificial graphite; The graphite has a carbon content of more than 99 weight %, an ash content of less than 1 %, and a mesh size of 20 to 500 meshes.
5. The method according to claim 1, wherein: The mass ratio of the concentrated acid to the graphite is (15-100):1, preferably (25-80):1; The mass ratio of the potassium permanganate to the graphite is (1-10):1, preferably (3-8):1; The mass ratio of potassium permanganate to the graphite mixed in each batch is (0.1-1):1, preferably (0.2-0.5):
1.
6. The method according to claim 1, wherein: The method further includes: In step S1, potassium permanganate is added in batches and mixed, and the temperature is controlled to be below 30° C., preferably below 20° C., and more preferably below 10° C., and stirred for 0.5 to 12 hours; sodium nitrate and hydrogen peroxide are not added during the reaction; In step S2, the conditions for the heating reaction are: temperature of 35-60°C, reaction time of 0.2-6h; and time for stirring after adding water of 0.1-5h.
7. The method according to claim 1, wherein: The mass ratio of the amount of water added to the amount of graphite added is (20-500):1, preferably (50-200):
1.
8. A manganese-containing graphene oxide composite material prepared by the method according to any one of claims 1 to 7.
9. The manganese-containing graphene oxide composite material according to claim 8, wherein: The manganese-containing graphene oxide composite material contains manganese, carbon, oxygen, potassium and sulfur. In the manganese-containing graphene oxide composite material, the content of manganese calculated as MnO2 is 55-90 weight %; the content of sulfur calculated as SO2 is 0.5-10 weight %; the content of potassium calculated as K2O is 1-15 weight %; The XRD spectrum of the manganese-containing graphene oxide composite material has a characteristic peak of α-MnO2; The specific surface area of the manganese-containing graphene oxide composite material is 300 to 800 m 2 / g, preferably 400 to 600 m 2 / g, the pore volume is 0.5 to 2 ml / g, preferably 0.8 to 1.5 ml / g, and the average particle size is 1 mm or less, preferably 0.5 mm or less.
10. Use of the manganese-containing graphene oxide composite material according to claim 8 or 9 in the removal of sulfur-containing compounds.
Citation Information
Patent Citations
A method for preparing graphene and manganese dioxide nanocomposite materials
CN102275903A
Preparation method of graphene modified nylon 6 fiber
CN103215689A
Method for preparing graphene oxide with controllable defects
CN106044750A
Method for preparing graphene through redox assisted by high-speed shearing
CN106517170A
Boiler flue gas desulfurization and denitrification method
CN112691537A
